The mechanics of a reasonably fitted quarterly New Keynesian macro model - Eric Mayer (University of Würzburg, Department of Economics, 2003)
The last years have witnessed a sharp increase of interest in monetary policy rules (see Taylor [1999]). This normative branch of monetary policy tries to evaluate the performance of alternative monetary policy rules in terms of associated monetary policy outcomes. Nevertheless this exercise is crucially based on the assumption that key parameters of the model are realistically specified. This holds in particular true for the preference vector of the central bank which trades off the individual goal variables of monetary policy and the degree of forward lookingness in the Phillips curve and the IS equation. Based on matching moments and the implied autocorrelations and cross correlations we present evidence for the USA covering the term of Allan Greenspan (1987:4- 2002:2) that hybrid specifications of the Phillips curve and the IS-curve are characterized by approximately 60% of backward looking economic agents. The predominant goal of monetary policy is price stability and financial market stability. Output gap stabilizationonly seems to play a minor role as an independent goal for the conduct of monetary policy.
Keywords: C51; E52; E58; 330; New Keyenesian Macro Model; hybrid Phillips curve; hybrid IS curve; forward looking behaviour; rule-of-thumb behaviour; calibration; Ungleichgewichtstheorie; Phillips-Kurve; Ökonometrisches Makromodell; Modell-Spezifikation; Theorie